ANALISIS PIDANA TAMBAHAN KEBIRI KIMIA DALAM UNDANGUNDANG NOMOR 17 TAHUN 2016 TENTANG PENETAPAN PERATURAN PEMERINTAH PENGGANTI UNDANGUNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK BERDASARKAN PERSPEKTIF HAK ASASI MANUSIA - Grace Tiur Esterella Silalahi; Mukhlis R; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Indonesian Criminal Law only recognizes two types of crimes, namely basic crimes andadditional crimes. Chemical castration is included in additional penalties in Indonesia which areregulated in Law Number 17 of 2016 concerning Stipulation of Government Regulations in Lieu ofLaw Number 23 of 2002 concerning Child Protection which provides weighting and additionalcriminal penalties for perpetrators of sexual violence against children as regulated in article 81paragraph 7 that